Analysis of Language Style in the Album “Uang Muka” by the Group Band Feast - Dewi Astri Amalia; Aini Puspita Astika; Dewi Nurfatimah; Salama Putri Anugrah; Sri Handayani; Buyung Firmansyah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
Music is a something that continues to evolve and influences the lives of Indonesian people. The album Uang Muka was popularized by the band .Feast is an album that conveys social criticism in its songs. The use of various language styles makes this song unique and provides a deep message to its listeners, but academic studies on this album are still limited. This analysis aims to identify the language style used in the album Uang Muka by the band .Feast. This study employed a qualitative descriptive methodology. Collection techniques such as scrutinizing, listening, and writing with the object of the research are song lyrics on the album. Data analysis techniques are conducted using content analysis methods. The research result of language style on the album Uang Muka by. Feast group with Gaya Bahasa Tarigan theory found 15 language styles. These styles include metaphor, personification, antithesis, hyperbole, satire, paradox, cynicism, sarcasm, litotes, epithet, synecdoche, alliteration, epistrophe, anaphora, and epizeukis. The use of language styles in the song lyrics seeks to create a beautiful impression while highlighting the intended message.